UKURAN PERUSAHAAN, PROFITABILITAS DAN NILAI PERUSAHAAN: STUDI EMPIRIK: PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011 SAMPAI DENGAN 2015) - Arkasmiralda Habsari; Akhmadi Akhmadi (Tirtayasa Ekonomika, 2018)
Purpose – This study is to provide information or description of the effect of firm size on the value of the company-mediated profitability in mining sub-sector companies listing on the Indonesia Stock Exchange period 2011-2015Design/methodology/approach – The sample selection in this study using nonprobability sampling, and obtained as many as 24 companies from the total population of 40 companies. Data analysis methods used are descriptive statistics, classical assumption test, and Path Analysis, and Sobel Test.Findings – The size of the company has a positive and significant impact on stock prices, firm size has no effect on profitability, profitability has a positive and significant impact on corporate value. While profitability is not able to mediate the relation of firm size to firm valueResearch limitation/implications – This research is only the mining sub-sector, while the problem on the value of the company occurs also in other sub-sectors. Then, the proxy used is only one for each of the observed variables. The period of 5 years is from 2011 to 2015, so the data taken there is less likely to reflect the condition of the company in the long run.Originality/value – Located on a research model that includes profitability as an intervening variable in the research modelKeywordsCorporate  Value, Firm Size, Profitability